Ethylene, a Signaling Compound Involved in Seed Germination and Dormancy - Françoise Corbineau (Plants)
The present review is focused on current findings on the involvement of ethylene in seed biology. The responsiveness of seeds to ethylene depends on the species and the dormancy status, improving concentrations ranging from 0.1 to 200 μL L−1. The signaling pathway of ethylene starts with its binding to five membrane-anchored receptors, which results in the deactivation of Constitutive Triple Response 1 (CTR1, a protein kinase) that does not exert its inhibitory effect on Ethylene Insensitive 2 (EIN2) by phosphorylating its cytosolic C-terminal domain. An analysis of germination in the presence of inhibitors of ethylene synthesis or action, and using seeds from mutant lines altered in terms of the genes involved in ethylene synthesis (acs) and the signaling pathway (etr1, ein2, ein4, ctr1 and erf1), demonstrates the involvement of ethylene in the regulation of seed dormancy. The promoting effect of ethylene is also regulated through crosstalk with abscisic acid (ABA) and gibberellins (GAs), essential hormones involved in seed germination and dormancy, and Reactive Oxygen Species (ROS). Using a mutant of the proteolytic N-degron pathway, Proteolysis (PRT6), the Ethylene Response Factors (ERFs) from group VII (HRE1, HRE2, RAP 2.2, RAP2.3 and RAP 2.12) have also been identified as being involved in seed insensitivity to ethylene. This review highlights the key roles of EIN2 and EIN3 in the ethylene signaling pathway and in interactions with different hormones and discusses the responsiveness of seeds to ethylene, depending on the species and the dormancy status.